Analisis Pengaruh Ketersediaan Produk, Fasilitas, Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian Konsumen Dalam Pembelian Bahan Bakar Minyak Jenis Pertalite Di Rantauprapat (Studi Kasus SPBU PT. Kusuma Jaya Makmur 14.214.225) - Juliany, Elsa (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
This study aims to analyze the effect of product availability, facilities, service quality and location on consumer purchasing decisions in the purchase of fuel oil pertalite type case study gas station PT Kusuma Jaya Makmur 14.214.225. The population in this study are consumers who do the pertalite type of fuel oil or who have done the filling directly at the gas station PT Kusuma Jaya Makmur 14.214.225 JL. Gen. Ahmad Yani, AH25, Bakaran Batu, Rantau Sel., Labuhan Batu Regency, North Sumatra. This study used a sample of 97 people. This study uses the method of incidental Sampling that is anyone who by chance met with the researcher can be used as a sample , if the person who happened to meet it is suitable as a source of data. In simultaneous testing (test F), it is known that the availability of products, facilities, service quality, and location have a positive and significant effect on purchasing decisions. Persially (t test) it is known that the availability of products, facilities, service quality, and location have a positive and significant effect on purchasing decisions. Through testing coefficient determinants obtained Adjusted R Square value of 0.828 or 83% of consumer purchasing decisions can be explained product availability, facilities, service quality, and location while the remaining 17% can be explained by other variables that are not discussed in this study. Feasibility testing of research instruments and descriptive analysis of respondents ' characteristics using SPSS software (Statistical Package for the Social Science) version 22.